Media influence on adolescents’ healthy nutrition in Lima district public schools - Román, Verónica (2010)
Introduction: Media have influence on the behavior of adolescents, and their messages can be enhancers or harmful to their health. Objectives: To determine the association of perceived media influence on healthy eating and belonging to Promoting Schools for Sustainable Development in adolescents. Desing: Descriptive, transversal and cross-association study. Location: Educational Institutions in Puente Piedra district. Participants: Male and female adolescents. Interventions: Three hundred and thirty adolescents chosen for convenience were divided equally whether they belonged or not to the program. Each adolescent answered a questionnaire about how they perceived media influence on healthy nutrition. Chi square was used to associate levels and Man-Whitney to compare scores between both groups. We used Excel 2003 and SPSS software 13.0. Main outcome measures: Scores for perceived media influence were 0–8 (low), 9–16 (medium), and 17–24 (high). Results: The ‘medium’ level had the highest percentage in both groups. The average score was 10.9 for those belonging to the program and 10.6 for those not belonging. The media that most influenced in the choice of food for both groups was television. The media that less influenced for those belonging to the program was newspaper and for those not belonging the radio. The family would influence in the choice of food in those belonging to the program and the media in those not belonging. Conclusions: There was no statistically significant difference between both groups.